2002
DOI: 10.1097/00000539-200202000-00041
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Cutaneous Distribution After Obturator Nerve Block

Abstract: Previous studies reporting an incidence of obturator nerve block after three-in-one block may have mistaken a femoral nerve block for an obturator nerve block in 100% of cases when the cutaneous distribution of the obturator nerve was assessed on the medial aspect of the thigh. The only way to effectively evaluate obturator nerve function is to assess adductor strength.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
58
1
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 8 publications
2
58
1
2
Order By: Relevance
“…Insufficient block of the obturator and lateral femoral cutaneous nerves in the SF 3-in-1 block may be one of the reasons for this difference. On the other hand, cutaneous distribution of the obturator nerve varies among patients and can be absent or incomplete in some patients [23]. Therefore, implication of the obturator nerve in pain manifestation after peripheral block with SF 3-in-1 and SPC seems less important than was thought previously.…”
Section: Discussionmentioning
confidence: 85%
“…Insufficient block of the obturator and lateral femoral cutaneous nerves in the SF 3-in-1 block may be one of the reasons for this difference. On the other hand, cutaneous distribution of the obturator nerve varies among patients and can be absent or incomplete in some patients [23]. Therefore, implication of the obturator nerve in pain manifestation after peripheral block with SF 3-in-1 and SPC seems less important than was thought previously.…”
Section: Discussionmentioning
confidence: 85%
“…*Statistically different from Group R and Group B. explain this discrepancy, it is possible that the large volume and the approach of the FNB used in the present study may be responsible for our results. In addition, the cutaneous distribution of the obturator nerve is not only highly variable but may even be incomplete or totally absent, suggesting that the obturator nerve does not contribute significantly to the postoperative pain of patients having undergone TKR [23,24]. However, further investigation is necessary to clarify this point.…”
Section: Discussionmentioning
confidence: 99%
“…Although the obturator nerve has been reported to be blocked better by the psoas compartment approach, we did not fi nd any difference between the groups. A discrepancy between the sensory and motor block can be a result of the high variation in the cutaneous distribution of the obturator nerve, as Bouaziz et al [14] have reported. During PCRA, the distribution of the sensory block changed with time in both groups.…”
Section: Discussionmentioning
confidence: 95%